Reading Comprehension and Linguistic Abilities of Children with and without Specific Learning Difficulties: Theoretical and Educational Implications - George Kritsotakis; Eleni Morfidi (MDPI AG, 2024)
The aim of the present study has been to investigate reading comprehension (RC) of children with specific learning difficulties (SLD), considering linguistic factors, such as receptive vocabulary, morphosyntax, and pragmatics (i.e., figurative language). Participants included 90 students (9-12 years old; Μyears = 10.8, SD = 0.95), 45 with SLD and 45 typically developing (TD) controls, matched on age, gender, and non-verbal cognitive ability. Results indicated that students with SLD had significantly lower performance on RC and across all linguistic measures compared to TD peers. Scores of the figurative language comprehension task predicted RC for TD children, whereas morphosyntactic ability emerged as a unique predictor of RC for SLD children. The two groups utilize distinct linguistic resources in their effort to extract meaning from written texts. The differentiated language profile of children with SLD suggests the implementation of differentiated educational assessment and intervention practices, which are discussed.